(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Aisyah SI, Oktavia AWP, Ayuningtyas AA, Putra RP, Prassiska S, Jamilah S, Nurcholis W. 2023. Short Communication: Differences in phytochemical compounds and antioxidant activity of Portulaca oleracea and Portulaca grandiflora. Biodiversitas 24: 1385-1390. Portulaca oleracea and Portulaca grandiflora are medicinal ornamental plants used in traditional and modern medicine. Therefore, this study aimed to analyze the phytochemical compounds and antioxidant activity in two purslane plants, P. oleracea,and P. grandiflora. The purslane ethanol extract was obtained by sonication and maceration methods. The phytochemical screening included the examination of secondary plant metabolites, while antioxidant activity was analyzed using the 2,2-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS) and cupric ion reducing antioxidant capacity (CUPRAC) methods. The results showed that both extract samples contain alkaloids, phenol hydroquinones, flavonoids, saponins, tannins, triterpenoids, and steroids. The highest ABTS antioxidant activity was found in P. grandiflora extract at 26.93 µmol TE/g FW compared to P. oleracea extract at 15.98 µmol TE/g FW. The highest CUPRAC antioxidant activity was found in the P. oleracea extract at 33.22 µmol TE/g FW, while in the P. grandiflora extract, it was 18.55 µmol TE/g FW. Based on the results, it was concluded that the chemical complexity of various purslane plants causes differences in the antioxidant capacity.